Nonequilibrium statistical Zubarev’s operator and Green’s functions for an inhomogeneous electron gas - Kostrobii, P.; Markovych, B.; Vasylenko, A.; Tokarchuk, M.; Rudavskii, Yu. (Condensed Matter Physics, 2006)
Nonequilibrium properties of an inhomogeneous electron gas are studied using the method of the nonequilibrium statistical operator by D.N. Zubarev. Generalized transport equations for the mean values of inhomogeneous operators of the electron number density, momentum density, and total energy density for weakly and strongly nonequilibrium states are obtained. We derive a chain of equations for the Green’s functions, which connects commutative time-dependent Green’s functions “density-density”, “momentum-momentum”, “enthalpy-enthalpy” with reduced Green’s functions of the generalized transport coefficients and with Green’s functions for higher order memory kernels in the case of a weakly nonequilibrium spatially inhomogeneous electron gas.